2022
DOI: 10.3233/jpd-223237
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in Parkinson’s Disease

Abstract: Microglia are the primary resident immune cells of the central nervous system. Neuropathological reports have identified augmented microglial activation in brains of patients with neurodegenerative disorders including Parkinson’s disease (PD). Extensive research over the years has strengthened the current view on microglia as a player in the pathogenesis of PD and other α-synucleinopathies. In this review, we summarize key findings of the recent three years on microglia in PD with specific relevance to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Indeed, previous positron emission tomography (PET)/magnetic resonance imaging (MRI) studies have already largely investigated the relationship between neuroinflammation and gray matter alterations in Alzheimer’s disease [ 29 31 ]. However, more recently a negative correlation between an increased microglia activation and gray matter volume reduction has been demonstrated also in alpha-synucleinopathies such as PD [ 32 ]. Accordingly, in vitro evidences have suggested that neuronal release of aggregated alpha-synuclein in the central nervous system may activate microglia with production of proinflammatory mediators increasing the rate of neurodegeneration [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous positron emission tomography (PET)/magnetic resonance imaging (MRI) studies have already largely investigated the relationship between neuroinflammation and gray matter alterations in Alzheimer’s disease [ 29 31 ]. However, more recently a negative correlation between an increased microglia activation and gray matter volume reduction has been demonstrated also in alpha-synucleinopathies such as PD [ 32 ]. Accordingly, in vitro evidences have suggested that neuronal release of aggregated alpha-synuclein in the central nervous system may activate microglia with production of proinflammatory mediators increasing the rate of neurodegeneration [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, more recently a negative correlation between an increased microglia activation and gray matter volume reduction has been demonstrated also in alpha-synucleinopathies such as PD [ 32 ]. Accordingly, in vitro evidences have suggested that neuronal release of aggregated alpha-synuclein in the central nervous system may activate microglia with production of proinflammatory mediators increasing the rate of neurodegeneration [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…PD is influenced by many factors including a mix of immunogenetics and the environment, such as infection history. In recent years, increasing evidence suggests an association with autoimmune conditions, with the involvement of the immune system or its aberrant responses in patients and various experimental models [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In this special issue, our authors highlight the latest research breakthroughs on the links between immune activation and neuroinflammation and PD, and discuss the challenges and novel therapeutic strategies targeting the immune system ISSN 1877-7171/$35.00 © 2022 -IOS Press.…”
mentioning
confidence: 99%
“…Activated microglia can present autoantigens to T cells through MHC class I and II molecules, thereby activating the adaptive immune system. They have also been demonstrated to play a role in the conversion of astrocytes into neurotoxic phenotypes [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation